Peran United Nations High Commissioner for Refugees (UNHCR) dalam Proses Resettlement Pengungsi Asing di Indonesia (Studi Kasus Pengungsi Afghanistan di Kota Pekanbaru) - Rozaliana Azura, Fitrisia Munir (UIR Press, 2023)
In this study, the researcher were discusses the resettlement process for foreign refugees in Indonesia (Study Case of Afghanistan’s Refugees in Pekanbaru city). The rampant conflicts that were happened currently, causes the people who lived in that country were terrified and felt uneasy to stay in their country. Because of that phenomenon, those people tried to find the save and secure places in other specific countries by seeking protection until the conflict in their country settled down. Indonesia is one of the countries that are available for the refugees to pass across, although Indonesia is not the country of destination that the refugees aim for. The reasons behind this were because, Indonesia is has not ratified the 1951 convention and the 1967 protocol. Pekanbaru city is one of the cities in Indonesia that provided the living space for the refugees, and the largest number of refugees in pekanbaru city came from Afghanistan. To settle this case, the refugees in Indonesia especially Afghanistan’s refugees in pekanbaru, the government were cooperated with the international organization called UNCHR (United Nation High Commisioner for Refugees). Pekanbaru city possess the role of instrument, arena, and the independent actor in the resettlement process for the Afghanistan’s refugees. This study used constructivism perspective as the main theory. The method used in this study was qualitative method with case study approach. The data was collected by observation, interview and literature review. UNCHR gave the solutions for the subtraction matter in handling the Afghanistan’s refugees such as Repatriation, Intregrasi Local, and Resettlement.